Kinetic Modelling of the Extraction of Antioxidants from Red Grape (Vitis vinifera L.) Pomace Using Aqueous Organic Acid Solutions - Makris, Dimitris (Journal of Agricultural Sciences (Belgrade), 2017)
Grape pomace is a food industry waste containing a high burden of antioxidant polyphenols and several methodologies have been developed for their efficient extraction. However, a sustainable and environmentally friendly process should involve recovery means composed of benign, non-toxic solvents. In this line, this study examined the extraction of antioxidants, by using aqueous acetic acid and citric solutions and monitoring the reducing power (PR) of the extracts. The aim was to assess the role of acid concentration in the extraction yield, employing kinetics. The kinetic model established enabled the reliable comparison of the extraction efficiency of acetic acid and citric acid solutions as a function of acid concentration. The results showed that citric acid solutions are more suitable for retrieving antioxidants from grape pomace. Using a 4% (w/v) citric acid solution, a maximum PR of 229.8 μM ascorbic acid equivalents per g of dry pomace could be achieved. This study showed for the first time that aqueous media used for extracting antioxidant substances from residual plant materials can be profoundly affected by the acidifying agent and its concentration.